The Concept of Religious Monotheism: The Personification and Symbolization of God in the Scriptures of Monotheistic Religions - Ramadhan, An-Najmi Fikri; Limbong, Rahmat IR.; Makarim, Muhammad Ghifari; Kusuma, Juwanda Adi (Jurnal Studi Agama, 2023)
Abstract This study aims to see how symbols or personifications can bridge profane things from God into human reality. Religious symbols as the embodiment of God have the highest sacred value because they are built by the structures of religious teachings originating from the texts of the scriptures. This research is limited to three religions because they have the same theological concept, namely monotheism and the approach used is qualitative based on library research-related sources, especially as primary data, are the holy books of each religion, namely the Vedas, Tipitaka, and Al-Qur'an. As an analytical tool to help compare the symbolization of God in the scriptures, the semiotic theory is used to analyze the symbols of each religion. The results of this study found that the theological concept of monotheism in symbols of Hinduism, Buddhism, and Islam has similarities and there are differences in Islam that do not symbolize God in the form of symbols or forms. In this case, the difference is due to the pattern of belief, worship, and communal structure patterns in the teachings of the holy books of each religion. Keywords: Symbol, Monotheism, Islam, Hindu, Budha Abstrak Penelitian ini bertujuan untuk melihat bagaimana simbol atau personifikasi dapat menjembatani hal-hal yang profan dari Tuhan ke dalam realitas manusia. Simbol-simbol agama sebagai perwujudan Tuhan memiliki nilai sakralitas yang tertinggi karena terbangun oleh struktur-struktur ajaran agama yang berasal dari teks kitab suci. Penelitian ini dibatasi pada tiga agama karena memiliki konsep teologis yang sama yaitu monoteisme dan pendekatan yang digunakan adalah kualitatif dengan berbasis library research dengam sumber yang terkait terutama sebagai data primer adalah kitab suci masing-masing agama yaitu Veda, Tipitaka dan Al-Qur’an. Sebagai alat analisis bantu membandingkan simbolisasi Tuhan dalam kitab suci, teori semiotik digunakan untuk menganalisis simbol dari masing-masing agama. Hasil penelitian ini ditemukan, konsep teologis monoteisme dalam simbol agama Hindu, Budha dan Islam memiliki persamaan dan terdapat perbedaan pada agama Islam yang tidak menyimbolkan Tuhan ke dalam bentuk simbol atau bentuk. Pada hal perbedaan tersebut disebabkan karena faktor pola struktur keyakinan, peribadahan, dan komunal dalam ajaran kitab suci dari masing-masing agama. Kata kunci: Simbol, Monoteisme, Islam, Hindu, Budha